GAMBARAN SIKAP PASANGAN USIA SUBUR (SUAMI) DALAM PENGUNAAN ALAT KONTRASEPSI KELUARGA BERENCANA ( VASEKTOMI ) DI DESA PANJUNAN KECAMATAN KALITIDU KABUPATEN BOJONEGORO DETERMINE THE ATTITUDE OVERVIEW OF FERTILE COUPLES (HUSBAND) IN THE USE OF CONTRACEPTIV - PATONAH, SITI; STIAWAN, ATIK; IMANU, PAULUS (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2016)
Contraception is a means to prevent pregnancy. One of contraception aimed at men is vasectomy. Choosing contraception requires various considerations that determine a rational attitude and behavior. Phenomena that occur in the village Panjunan distric Kalitidu, mostly fertile couples (husband) did not use contraception because they believe its use is inappropriate for men.The puporse of this study was to determine the attitude overview of fertile couples (husband) in the use of contraceptives (vasectomy) in village Panjunan district Kalitidu 2014. This study used a descriptive method with a population of 90 people and 41 samples were taken by means of purposive sampling technique. Data were collected by questionnaire and then do the editing, coding, scoring, tabulating and measured with a Likert scale. The results of this study showed that the attitude of fertile couples (husband) in village Panjunan district Kalitidu more than the majority of respondents being unfavorabel (negative attitude) or do not support. Most couples of childbearing age do not support the use of contraception (vasectomy). Expected to fertile couples (husband) should increase knowledge and awareness of themselves by asking health workers in terms of health education, especially the use of contraception (vasectomy).